Asymptomatic Deep Vein Thrombosis is Associated with an Increased Risk of Death: Insights from the APEX Trial - Kalayci, Arzu; Gibson, C Michael; Chi, Gerald; Yee, Megan K; Korjian, Serge; Datta, Sudarshana; Nafee, Tarek; Gurin, Mike; Haroian, Noah; Qamar, Iqra; Hull, Russell D; Hernandez, Adrian F; et al. (Thrombosis and haemostasis, 2018)
Asymptomatic deep vein thrombosis (DVT) diagnosed with compression ultrasound (CUS) is a common endpoint in trials assessing the efficacy of anticoagulants to prevent venous thromboembolism (VTE), but the relationship of asymptomatic thrombus to mortality remains uncertain. In the APEX trial (ClinicalTrials.gov: NCT01583218), 7,513 acutely ill hospitalized medical patients were randomly assigned to extended-duration betrixaban (35-42 days) or enoxaparin (10 ± 4 days). Asymptomatic DVT was assessed once with CUS between day 32 and 47, and mortality was assessed through 77 days. A total of 309 asymptomatic DVTs were detected through CUS. Of these, 133 (4.27%) subjects were in the betrixaban group, and 176 (5.55%) subjects were in the enoxaparin group (relative risk = 0.77, 95% confidence interval [CI] = 0.62-0.97, = 0.025, number needed to treat = 79). With respect to all-cause mortality due to cardiovascular diseases, non-cardiovascular diseases and unknown causes, the number of the deaths was 5 (1.67%), 4 (1.34%) and 1 (0.33%) in the asymptomatic DVT group and 25 (0.42%), 33 (0.56%) and 11 (0.19%) in the no DVT group, respectively. Subjects with an asymptomatic DVT had an almost threefold increase in the risk of all-cause mortality compared with subjects without DVT (hazard ratio = 2.87, 95% CI = 1.48-5.57, = 0.001). A positive linear trend was observed between greater thrombus burden and mortality during the follow-up ( = 0.019). Asymptomatic DVT was associated with approximately threefold increased risk of short-term all-cause mortality in patients hospitalized with an acute medical illness within the prior 77 days. A positive linear trend was observed between greater thrombus burden and mortality during the follow-up.